Pollution of the waters of the Rímac river: traces of metals - Guillén, Oscar (1998)
Knowledge of the aquatic environment, as well as the main sources of contamination, its transport, its transfer and bioaccumulation are necessary for an adequate evaluation of the degree of contamination of the waters of the Rímac River and its effects on hydrobiological resources and human health. The waters of the Rímac River are mainly contaminated by residues from the mining-metallurgical industry, domestic waste from the centers located on its banks, industrial and agricultural waste. Likewise, the growing requirement for drinking water to supply the population of Lima and Callao, for agriculture and energy generation, makes it necessary to carry out studies on the quality of water and its effects on hydrobiological resources and human health.